Oxidative Stress: A Link between Diabetes Mellitus and Periodontal Disease - Adriana Monea; Tibor Mezei; Sorin Popsor; Monica Monea (International Journal of Endocrinology)
Objective. To investigate oxidative stress (OS) and histological changes that occur in the periodontium of subjects with type 2 diabetes mellitus without signs of periodontal disease and to establish if oxidative stress is a possible link between diabetes mellitus and periodontal changes. Materials and Methods. Tissue samples from ten adult patients with type 2 diabetes mellitus (T2D) and eight healthy adults were harvested. The specimens were examined by microscope using standard hematoxylin-eosin stain, at various magnifications, and investigated for tissue levels of malondialdehyde (MDA) and glutathione (GSH). Results. Our results showed that periodontal tissues in patients with T2D present significant inflammation, affecting both epithelial and connective tissues. Mean MDA tissue levels were 3.578 ± 0.60 SD in diabetics versus 0.406 ± 0.27 SD in controls (P < 0.0001), while mean GSH tissue levels were 2.48 ± 1.02 SD in diabetics versus 9.7875 ± 2.42 SD in controls (P < 0.0001). Conclusion. Diabetic subjects had higher MDA levels in their periodontal tissues, suggesting an increased lipid peroxidation in T2D, and decreased GSH tissue levels, suggesting an alteration of the local antioxidant defense mechanism. These results are in concordance with the histological changes that we found in periodontal tissues of diabetic subjects, confirming the hypothesis of OS implication, as a correlation between periodontal disease incidence and T2D.